2018
DOI: 10.1186/s12964-018-0226-1
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 (MMP9) is involved in the TNF-α-induced fusion of human M13SV1-Cre breast epithelial cells and human MDA-MB-435-pFDR1 cancer cells

Abstract: BackgroundIn addition to physiological events such as fertilisation, placentation, osteoclastogenesis, or tissue regeneration/wound healing, cell fusion is involved in pathophysiological conditions such as cancer. Cell fusion, which applies to both the proteins and conditions that induce the merging of two or more cells, is not a fully understood process. Inflammation/pro-inflammatory cytokines might be a positive trigger for cell fusion. Using a Cre-LoxP-based cell fusion assay we demonstrated that the fusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 47 publications
6
55
0
2
Order By: Relevance
“…The Kaplan-Meier analysis results showed that higher levels of MMP9, CSF1R, and PTPRC were related to shorter survival time of TGCT patients. MMP9 is a class of enzymes involved in the degradation of the extracellular matrix, which was up-regulated in tumor tissue samples of multi cancer [59][60][61], such as TGCT [62], breast cancer [63], lung cancer [64]. Moreover, MMP9 overexpression was significantly associated with poor survival of nasopharyngeal carcinoma [65] and glioblastoma [66].…”
Section: Ppimentioning
confidence: 99%
“…The Kaplan-Meier analysis results showed that higher levels of MMP9, CSF1R, and PTPRC were related to shorter survival time of TGCT patients. MMP9 is a class of enzymes involved in the degradation of the extracellular matrix, which was up-regulated in tumor tissue samples of multi cancer [59][60][61], such as TGCT [62], breast cancer [63], lung cancer [64]. Moreover, MMP9 overexpression was significantly associated with poor survival of nasopharyngeal carcinoma [65] and glioblastoma [66].…”
Section: Ppimentioning
confidence: 99%
“…Numerous studies further showed that the frequency of cell fusion events was increased upon acute tissue damage or chronic inflammation [7,12,18,32,63,64,[72][73][74][75], which is plausible with regard to efficient BMSC-based and cell fusion-mediated tissue regeneration. BMSCs not only have to be converted into a pro-fusogenic state for subsequent hybridization with target cells but also have to be recruited to the site of tissue damage.…”
Section: How Do Cells Fuse With Each Other?mentioning
confidence: 96%
“…Osteoclastogenesis [70,74,75], as well as the fusion of cancer cells with endothelial cells [63,76], mesenchymal stem cells [64], or breast epithelial cells [72,73,77] can be induced by TNF-α. Some data revealed that TNF-α could mediate fusion due to induction of MMP-9 expression [73,75], which plays a role in osteoclastogenesis and giant cell formation [75,78]. Hence, it might be assumed that TNF-α could be involved in cell fusion due to induction of pro-fusogenic proteins and/or in an overall conversion of cells into a pro-fusogenic state.…”
Section: How Do Cells Fuse With Each Other?mentioning
confidence: 99%
“…Mehrere Studien deuten auf einen Zusammenhang zwischen Inflammation/ inflammatorische Mediatoren und Zellfusion hin [19,47,61,65,81,90]. Sowohl Johansson et al als auch Davies et al konnten in tierexperimentellen Studien belegen, dass die Fre quenz von Zellfusionsereignissen in Gegenwart von inflammatori schen Konditionen mitunter bis um den Faktor 100 erhöht war im Vergleich zu entsprechenden Kontrollstudien [19,47].…”
Section: Makrophageunclassified
“…Sowohl Johansson et al als auch Davies et al konnten in tierexperimentellen Studien belegen, dass die Fre quenz von Zellfusionsereignissen in Gegenwart von inflammatori schen Konditionen mitunter bis um den Faktor 100 erhöht war im Vergleich zu entsprechenden Kontrollstudien [19,47]. Speziell für das pro-inflammatorische Zytokin TNF-α konnte ein pro-fusioge ner Effekt beobachtet werden, was sowohl die Fusion von Makro phagen als auch die Fusion von Tumorzellen mit anderen Zellen be trifft [61,65,81,90]. Auch in chronisch entzündetem Gewebe kommt es zu einer erhöhten Frequenz von Zellfusionsereignissen [47,59,69], da die Zellfusion, wie oben erwähnt, eine Rolle in der Geweberegeneration/ Wundheilung spielt und durch inflammato rische Prozesse begünstigt wird.…”
Section: Makrophageunclassified